Peucedanum shanianum, a new replaced name for P. rubricaule R.H. Shan & M.L. Sheh (Apiaceae) - Chen, Fenglin; Deng, Yunfei (Phytotaxa, 2019)
Peucedanum Linnaeus (1753: 245) is a complex genus with 100–120 species in the subfamily Apioideae of the family Apiaceae (Pimenov & Leonov 1993; Spalik et al. 2004; Sheh & Watson 2005). The genus is distributed in Eurasia and Africa and is characterised by ﬂattened fruits with more or less developed lateral wings (Spalik et al. 2004). Fourty species, with 33 endemics, are recorded in China (Sheh & Watson 2005; Liu 2016).